A Comparative Study on the Factors Controlling the Cusp Auroral Intensity Between the Northern and Southern Hemispheres. Issue 4 (18th April 2022) - Qiu, Hui‐Xuan; Han, De‐Sheng; Zhang, Hong‐Da; Yang, Hui‐Gen; Feng, Hui‐Ting; Yu, Xi; Shi, Run; Zhou, Su; Zhang, Y.‐L.
Abstract: The previous study has indicated that the interplanetary magnetic field (IMF) By and solar wind flow speed (Vsw ) have crucial effects on the cusp auroral intensity in the Northern Hemisphere. However, it is not clear how these factors influence the cusp aurora in the Southern Hemisphere. Using DMSP/SUSSI observations from 2004 to 2017 during non‐storm periods, we compared the factors affecting the intensity of cusp aurora between the Northern and Southern Hemispheres by dividing the observations into weak‐ and intense‐emission events. We found that the auroral intensity in the southern cusp: (a) has a positive correlation with solar wind power input, (b) is statistically weak under southward IMF conditions, and (c) is critically controlled by the IMF By and Vsw . These results are essentially consistent with those obtained in the Northern Hemisphere. However, the IMF By effect shows apparent interhemispheric asymmetry, that is, the IMF By effect reaches the maximum at 2 nT in the Northern Hemisphere, but at −2 nT in the Southern Hemisphere. Further analysis shows that the 2‐nT deviations disappear after dividing all events by season and the IMF By distributions of intense‐emission events show clear seasonal difference. Based on these results, we suggest that the dependence of the cusp auroral intensity on the IMF By is not only controlled by −Vsw × By field, but also affected by season. Plain Language Summary: As one of the most important regions in the magnetosphere, the polar cusp is the direct entry of the solar wind particles entering the Earth. The cusp aurora is produced by the interaction of the solar wind particles and the neutral particles in the upper atmosphere. Therefore, the intensity of the cusp aurora is significantly influenced by solar wind power input. According to previous research, solar wind power input can be well measured by the solar wind speed, the interplanetary field magnitude, and the IMF direction together, and the dependence of the cusp auroral intensity on these factors has also been widely investigated. A recent work statistically analyzed the occurrence conditions, that is, the solar wind and IMF conditions, for "auroral midday gap" observed above the Northern Hemisphere. It revealed that the IMF By component is vital in enhancing the auroral emissions near the cusp. However, whether these factors have the same effects in the Southern Hemisphere is still unclear. In this study, we made an interhemispheric comparison of the interplanetary factors affecting the cusp auroral intensity. Some new results were obtained, and they are important for fully understanding the cusp aurora. Key Points: Among factors deciding solar wind power input, the IMF By is confirmed to critically control cusp auroral intensity in both hemispheres The dependence of the cusp aurora on the IMF By shows clear interhemispheric asymmetry and seasonal difference The interhemispheric asymmetry of the IMF By effect is affected by both the −Vsw × By electric field and the season